Point-of-care colorimetric glucose biosensor using Cu-MOF@N-doped graphite nanoparticles with enhanced peroxidase-like activity - Shymaa S. Soliman; Mona A. Abdel Rahman; Amr M. Mahmoud; Norhan Badr ElDin; Dina A. El Mously (Sensing and Bio-Sensing Research)
The metal-organic frameworks (MOFs) have many appealing characteristics as biomimetic enzymes for colorimetric glucose detection, such as their large surface areas, distinct pore structures, chemical composition that can be adjusted, and multifunctional sites. In the current study, a Cu-MOF@N-dGr with peroxidase-mimicking activity was synthesized to design a colorimetric assay for glucose detection. The Cu-MOF@N-dGr was prepared in a two-step process, firstly, nitrogen-doped graphite was synthesized using soft-nitriding and secondly, a solvothermal method was adopted to anchor Cu-MOF on the N-dGr surface. It was possible to detect both H2O2 and glucose with an effective linear range of 0.08 mM to 1.12 mM and 0.16 mM to 0.83 mM, respectively. Various techniques were utilized to analyze the synthesized N-doped graphite Cu-MOF's structure including scanning electron microscope (SEM), Energy-dispersive X-ray spectroscopy (EDX), Brunauer–Emmett–Teller (BET) and x-ray photoelectron spectroscopy (XPS). This recently developed Cu-MOF@N-dGr offers an easy-to-use, sensitive, and selective colorimetric analysis method for measuring glucose and determining hydrogen peroxide for point-of-care applications.